ANALISA MATERI QUR’AN HADIS MADRASAH ALIYAH DENGAN PENDEKATAN INTERDIPISPLINER - Muhammad Mahbub (Jurnal Ilmu Pendidikan Islam, 2021)
Curriculum is a set of plans and arrangements regarding objectives, content and materials and methods used in the learning and assessment process to achieve certain desired goals. Al Qur'an and Hadith as an integral part of the Religious Education curriculum at Madrasah Aliyah if learning is carried out effectively and meaningfully, it is hoped that students will be able to solve their religious problems in the community, students will become part of the solution, not the problem. However, the reality that is currently developing is that many Madrasah Aliyah graduates do not have integrity and independence in their religion, belief and religion, which actually becomes a problem for other people, even other groups. So this is where it is necessary to redesign teaching materials as media that provide knowledge, skills and attitudes to students, not only using interpretive analysis as the basis for the conception of the material, but also connecting with other disciplines, synergizing with socio-cultural, political, economic and even religious teachings. other materials that intersect with the material, so that the concept of the material being taught becomes very close to the environment and students' needs. On this basis, the analysis of teaching materials absolutely must use an interdisciplinary approach in unraveling the concept of the verse text side by side with the content of the analysis in the meaning of the verse text. Keywords: al Quran-Hadith, material conception, interdisciplinary